Surveillance and Genomic Characterisation of Colistin-Resistant Gram-Negative Bacteria in the Drains of High-Risk Hospital Units - Giuseppe Fleres; Alessia Mirabile; Mariëtte Lokate; John W.A. Rossen; Natacha Couto; Alexander W. Friedrich; Silvia García-Cobos (Journal of Global Antimicrobial Resistance)
ABSTRACT: Objective: The health care water environment, including sinks and drainage systems, can be a long-term reservoir of nosocomial pathogens. In this study, we aimed to investigate the presence of colistin-resistant Gram-negative (ColR-GN) bacteria in humid compartments of high-risk hospital units at the University Medical Center Groningen, The Netherlands. Methods: Environmental sampling was conducted in sink and shower drains of high-risk hospital units, and colistin MICs were determined using broth microdilution. Whole-genome sequencing was performed to investigate the presence of mobile colistin resistance (mcr) genes, chromosomal point mutations and gene alterations linked to colistin resistance. Results: ColR-GN bacteria were detected in all investigated units, with Enterobacter spp. being the most abundant genus. Twelve isolates exhibited colistin resistance (MIC >2 mg/L), including Enterobacter cloacae complex (n = 11) and Klebsiella pneumoniae (n = 1). Chromosomal mutations in genes involved in lipopolysaccharide structure modifications were the main mechanisms contributing to colistin resistance in Enterobacter spp. and Klebsiella spp. (91.6%, 11/12). Additionally, two Enterobacter kobei isolates harboured mobile colistin resistance genes, mcr-4.3 and mcr-9.1. Conclusions: The presence and persistence of bacterial ColR-GN clones in the sink and shower drains of high-risk hospital units highlights the importance of monitoring such environments for antibiotic-resistant bacteria to identify reservoirs and prevent further spread.